Ene Reaction of Nitrosocarbonyl Mesitylene with the Cinnamyl Alcohol: Metabolic Activity and Apoptosis of the Synthetized 6-Chloropurine N,O-Nucleoside Analogues - Memeo, Misal Giuseppe (ACS Omega, 2018)
[Image: see text] Nitrosocarbonyl mesitylene intermediate undergoes an ene reaction with cinnamyl alcohol affording the corresponding 5-hydroxy-isoxazolidine in fair yields. The synthesized 5-acetoxy-isoxazolidine serves as synthon for the preparation of 6-chloropurine N,O-nucleoside analogues, according to the Vorbrüggen reaction. The compounds were evaluated for their metabolic and apoptotic activity, and their structure–activity relationship is discussed.